ANALISIS PENDAPATAN USAHATANI JAGUNG DI DESA PAKUWERU KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - Melfan Michel Ratag; Gene Henfried Meyer Kapantow; Elsje Pauline Manginsela (AGRI-SOSIOEKONOMI, 2021)
This study aims to analyze the income of corn farming in Pakuweru Village, Tenga District, South Minahasa Regency. The data used in this research are primary data and secondary data. Primary data were obtained from direct interviews with farmers using a questionnaire. The number of respondents was 9 corn farmers out of a total of 91 farmers. Respondents were selected using the Purposive Sampling Method, with the sample criteria being those who planted corn during the pandemic and the harvest was in August 2020. The sample farmers were divided into two categories according to the planted area. The first category is those who have a planting area of 2 hectares and below, while the second category is those who have a planting area of more than 2 hectares. The results showed that the average income per farmer in the first category, which has a planting area of 2 hectares and below, is Rp. 356,450, or Rp. 254,607/ha, while for the second category, namely farming with a planting area of more than 2 hectares, the average income per farmer is Rp. 17,699,835, with an average income per hectare of Rp. 3,371,398. So the average income per hectare of corn farming with a planting area of more than 2 hectares is much higher than that of a farm with a planting area of 2 hectares and below.